Correlation of the stock pile dimmensions with equipment parameters - Gruneantu, I.; Ilias, N.; Radu, S.; Andras, I.; Jujan, C. (НТУ "ХПИ", 2010)
The coal warehouses which have formed as a result of operation of deposits, are necessary structural elements of the making branches, processing or consuming. In work the concept of measurement and realization of the warehouses, described is presented by simplicity, peak efficiency and the minimal investment volume.

The coal warehouses which have formed as a result of operation of deposits, are necessary structural elements of the making branches, processing or consuming. In work the concept of measurement and realization of the warehouses, described is presented by simplicity, peak efficiency and the minimal investment volume.
Определение размеров угольных складов в зависимости от характеристики оборудования
Keywords: coal warehouses; minimal investment volume; peak efficiency; угольные склады; эксплуатация месторождений; максимальная эффективность; минимальный инвестиционный обьем